Effects of welding technique, filler metal and post-weld heat treatment on stainless steel and mild steel dissimilar welding joint. (April 2021) - Khan, Mahmud; Dewan, Mohammad Washim; Sarkar, Md. Zahidul
Abstract: Joining of two materials having different physical, chemical, and thermal properties and to make the joint tough and stiff, special attention and investigation are required. In this research, the welding joint between stainless steel (SS) of grade AISI 304 and mild steel (MS) of grade AISI 1020, was accomplished by using shielded metal arc welding (SMAW) and tungsten inert gas (TIG) welding process. To investigate the effect of filler material in the dissimilar welding joint, both MS and SS filler material was exercised. For post-weld heat treatment (PWHT), three distinct temperatures of 600 °C, 630 °C, and 650 °C were investigated over the welded specimens. To explore the optimum welding process and PWHT process for this dissimilar joint, both tensile and bending tests were carried out. Destructive tests have suggested that PWHT at 630 °C is better for the SMAW process with both MS and SS electrodes and PWHT at 600 °C is more suitable for TIG welding process with both MS and SS filler rod. Both optical and SEM micrographs showed that the amount of δ ferrite and martensite is higher in the as-welded situation. The coarser grain structure was observed in the heat-affected zone (HAZ) which makes the sample susceptible to failure. This is the region where the hardness values were the smallest. The hardness values have decreased after PWHT which justified the achievement of higher ductility after heat treatment. After conducting fracture analysis by SEM, it has been noticed the specimen becomes more ductile after PWHT. The best solution based on the mechanical, microstructural, and fracture analysis concluded that TIG welding with MS filler rod and PWHT at 600 °C is the optimum condition for joining SS AISI 304 with MS AISI 1020.